2016
DOI: 10.1007/s11325-016-1447-4
|View full text |Cite
|
Sign up to set email alerts
|

The gender difference of snore distribution and increased tendency to snore in women with menopausal syndrome: a general population study

Abstract: PurposeSleep-disordered breathing (SDB) is a prevalent disorder with a major impact in women, especially postmenopausal women. However, few studies have investigated the prevalence of a specific SDB, snoring, among women especially those with menopausal syndrome.MethodsComputer-assisted telephone interviews were conducted in Taiwan. Adults over 20 years of age were interviewed. The number of successful interviews was calculated based on the population prior to the study. Demographic data and information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…It has been said that the prevalence of snoring is gender-dependent and increases with advancing age and BMI ( 1 , 2 , 7 ). It has also been reported that the snoring frequency increases in both male and female Asian subjects up to 59 years of age ( 8 ). Similar results were obtained in this study.…”
Section: Discussionmentioning
confidence: 91%
“…It has been said that the prevalence of snoring is gender-dependent and increases with advancing age and BMI ( 1 , 2 , 7 ). It has also been reported that the snoring frequency increases in both male and female Asian subjects up to 59 years of age ( 8 ). Similar results were obtained in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of sleep apnea peaks in clinical populations around 55 years for men and 65 years for women. [34]…”
Section: Discussionmentioning
confidence: 99%
“…snoring in women increases significantly in women after the age of 50 years, and the overall decline in prevalence after age 59 years compared with men is less steep. 10 The age of 50 years corresponds to the start of menopause, which has been associated with increased risk of OSA and will be discussed later. 11 In contrast, the prevalence of nocturia is higher in women compared with men.…”
Section: Osa Symptoms In Womenmentioning
confidence: 99%